Response of Maize (Zea mays L.) to Nitrogen and Zinc Fertilization in Minna, Nigeria. - Afolabi, Saheed G. (Journal of Agricultural Sciences (Belgrade), 2019)
A field experiment was conducted in 2014 and 2015 cropping seasons at the Teaching and Research Farm of the Federal University of Technology, Minna to evaluate the effects of different rates of nitrogen (N) and zinc (Zn) on the growth and yield of maize. The treatments were four levels of N; 0, 60, 90 and 120 kg ha-1 and three levels of Zn; 0, 2.5 and 5 kg ha-1. The experimental design was a 4 x 3 factorial fitted in a randomised complete block design with three replications. The soil was relatively low in initial N content and relatively high in soil extractable Zn of 2.30 mg kg-1. The main effect of N on the growth of maize was significant (p